Adaptogenic potential of Centella lujica supplement in sleep deprived mice - Eduviere, Anthony T.; Awhin, Prosper E.; Edje, Kesiena E.; Otomewo, Lily O.; Adeoluwa, Olusegun A.; Winter, Jennifer E. (International Journal of Research in Medical Sciences, 2021)
Background: Stress, whether internal or external, has been shown to play a role in the accumulation of oxidative free radicals which leads to cellular modification of normal organ or body function. Centella lujica (C. lujica) is a commonly cultivated herb with therapeutic benefits in various studies. This study aims to evaluate its beneficial effect on the brain and liver of mice exposed to sleep deprivation-induced stress. Methods: Albino mice were treated with distilled water (control), C. lujica (50 and 100 mg/kg) or astaxanthin (50 mg/kg) for seven days. All groups except control were then subjected to three-days of sleep deprivation using the grid suspended over water model beginning from day 4 of treatment. Behavioural assessments followed by biochemical assays and histological analysis were carried out thereafter. Results: Sleep deprivation caused an increase in blood glucose and triglycerides levels but reduced high density lipoproteins. Brain pro-oxidant levels were increased with a concomitant decrease in antioxidants, recognition memory was diminished while depressive-like symptoms were enhanced and neuronal viability of hippocampal CA1 as well as prefrontal cortex cells was reduced in sleep-deprived mice. However, supplementation with C. lujica reversed these effects as significantly as astaxanthin. Conclusions: C. lujica possesses antioxidant property that makes it an effective adaptogen against stress induced responses in mice.